Structural member and method for manufacturing the same
Patent Information
- Application Number
- JP2023139594
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-03-13
AI Technical Summary
【0008】 本発明により、多孔質の繊維強化樹脂からなる構造部材において、マトリクス樹脂に含まれる低分子化合物の拡散を抑制することができる。さらに、本発明の構造部材は、空気中に存在する低分子化合物を捕捉することも可能である。
Smart Images

Figure 2025033692000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a structural member consisting essentially of a porous fiber-reinforced resin. [Background technology]
[0002] Fiber-reinforced composite materials, which use a reinforced fiber base material as the reinforcing material and impregnate the pores with a matrix resin, are lightweight yet have excellent mechanical properties such as strength and elastic modulus. They are used as structural members in many fields, including aerospace, automobiles, railway vehicles, ships, electronic devices, industrial machinery, sporting goods, and civil engineering and construction.
[0003] Among them, a nonwoven reinforcing fiber substrate can be used as a structural member by expanding due to springback when pressure is removed after impregnation with a matrix resin. Since such a structural member has a structure in which the reinforcing fibers reinforce the pores, it is possible to make it very lightweight while maintaining a considerable degree of mechanical properties, and it is expected to be a new structural member. For example, Patent Document 1 discloses a structure consisting of a resin, reinforcing fibers, and voids. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2017 / 110528 Summary of the Invention [Problem to be solved by the invention]
[0005] On the other hand, because such structural members have a large specific surface area, a large area of the matrix resin in the pores is exposed to the outside air. Therefore, decomposition products of the matrix resin and low molecular weight compounds contained in the matrix resin tend to diffuse into the air as gas. For example, if the matrix resin contains phenolic resin, there is a possibility that formaldehyde will be gradually released.
[0006] An object of the present invention is to provide a structural member which combines light weight, mechanical properties, and the effect of suppressing gas emission. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention provides a structural member made of a porous fiber-reinforced resin containing reinforcing fibers, resin, and continuous pores, in which the resin is present in an amount of 100 to 1,000 parts by mass per 100 parts by mass of the reinforcing fibers, and a gas adsorbent compound is fixed to the porous surface facing the continuous pores. Effect of the Invention
[0008] According to the present invention, in a structural member made of a porous fiber-reinforced resin, it is possible to suppress the diffusion of low molecular weight compounds contained in a matrix resin. Furthermore, the structural member of the present invention is also capable of capturing low molecular weight compounds present in the air. [Brief description of the drawings]
[0009] [Figure 1] Schematic diagram showing one embodiment of a fiber-reinforced resin in the present invention. [Diagram 2] FIG. 1 is a schematic diagram showing an embodiment of a structural member of the present invention; [Diagram 3] FIG. 1 is a schematic diagram showing an embodiment of a structural member of the present invention; [Figure 4] Schematic diagram showing one embodiment of a reinforcing fiber substrate in the present invention. [Diagram 5] Schematic diagram showing one embodiment of a prepreg according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] <Structural components> The structural member of the present invention is essentially composed of a porous fiber-reinforced resin containing reinforcing fibers, resin, and continuous pores. Here, "essentially composed of a porous fiber-reinforced resin containing reinforcing fibers, resin, and continuous pores" means that as long as the majority of the skeleton of the structural member is such a fiber-reinforced resin, it does not exclude embodiments that contain other elements such as a gas adsorbing compound described below. In addition, when the term "fiber-reinforced resin" is used in this specification without any special specification, it refers only to the part that constitutes the skeleton of the structural member, not including other elements such as a gas adsorbing compound.
[0011] The fiber reinforced resin constituting the structural member of the present invention contains 100 to 1,000 parts by mass of resin per 100 parts by mass of reinforcing fiber. The amount of resin is more preferably 100 to 800 parts by mass, further preferably 200 to 800 parts by mass, and particularly preferably 200 to 400 parts by mass. If the amount of resin is more than this range, the light weight of the structural member made of fiber reinforced resin tends to be impaired. Also, if the amount of resin is less than this range, the mechanical properties of the structural member tend to be insufficient.
[0012] Fig. 1 is a schematic diagram showing one embodiment of such a fiber-reinforced resin together with an enlarged cross section of a single yarn of the reinforcing fiber. In this embodiment, the reinforcing fibers 1 are randomly dispersed to form a network, and the surface of the network is covered with the resin 2 to form the fiber-reinforced resin. The fiber-reinforced resin has continuous pores 3 as regions where neither the reinforcing fibers 1 nor the resin 2 are present. In other words, the periphery of the continuous pores 3 is reinforced by the reinforcing fibers 1 and the resin 2.
[0013] In the structural member of the present invention, a gas adsorbent compound having a property of adsorbing gas is fixed to the porous surface facing the continuous pores 3 of the fiber reinforced resin as described above. FIG. 2 is a schematic diagram showing an embodiment of the structural member of the present invention together with an enlarged view of a single yarn cross section of the reinforcing fiber. The gas adsorbent compound 4 may be present on the surface facing the continuous pores 3 in the porous structure constituted by the reinforcing fiber 1 or the resin 2, but typically, as shown in FIG. 2, the reinforcing fiber 1 is covered by the resin 2, and the gas adsorbent compound 4 further covers the surface of the resin 2. By interposing the gas adsorbent compound 4 between the resin 2 and the continuous pores 3 as shown in FIG. 2, it is possible to suppress the exposure of the resin, and by adopting such a structure, the gas adsorbent compound 4 can efficiently adsorb the gas generated from the resin 2.
[0014] In this specification, the term "the gas adsorbent compound is fixed" means that, when observed with a scanning electron microscope, the gas adsorbent compound is observed to completely or partially cover the porous surface of the fiber reinforced resin composed of the reinforcing fiber 1 or the resin 2. TOF-SIMS or SEM-EDX can be used to identify the gas adsorbent compound.
[0015] Here, FIG. 2 is a schematic diagram showing the state where the gas adsorbing compound covers the porous surface of the fiber reinforced resin entirely, and FIG. 3 is a schematic diagram showing the state where the gas adsorbing compound covers the porous surface of the fiber reinforced resin partially. In the embodiment shown in FIG. 3, the outermost layer of the resin 2 is only partially covered with the gas adsorbing compound 4, and the remaining part is in contact with the continuous pores 3. The gas diffused from the resin 2 passes through the continuous pores 3 in the process until it is released to the outside of the structural member, and at this time, it repeatedly comes into contact with the gas adsorbing compound 4. Therefore, even if the coverage with the gas adsorbing compound 4 is partial, a certain effect is exhibited. The coverage rate with the gas adsorbing compound is preferably 50 to 100% of the surface of the fiber reinforced resin, more preferably 90 to 100%, and even more preferably 100%. This coverage rate can be measured by the method described in the examples described later.
[0016] The structural member of the present invention has a specific surface area of 0.01 to 1 m2, which can be measured by mercury intrusion porosimetry.2 / g. The specific surface area is preferably 0.01 to 0.5 m 2 / g is preferable, and 0.01 to 0.15m 2 / g is more preferable, and 0.05 to 0.15 m 2 / g is even more preferable. If the specific surface area is larger than this range, the mechanical properties such as the elastic modulus of the resulting structural member may be reduced. If the specific surface area is smaller than this range, the light weight may be reduced, and the gas adsorption effect of the gas adsorbing compound may be reduced. Mercury intrusion porosimeter is a method for measuring pores, in which mercury is injected into a sample at high pressure, and the pore distribution can be obtained from the applied pressure and the amount of mercury injected. The specific surface area is a value that can be calculated from the following formula (1). (specific surface area) = 4 × (pore volume) / (average pore diameter) (1).
[0017] In the present invention, the gas adsorbent compound is not particularly limited as long as it is a compound having some gas adsorption property, but is typically a compound having the property of adsorbing a gas containing molecules composed of two or more kinds of atoms. The adsorption mechanism here is preferably a chemical reaction between the gas and the gas adsorbent compound. By making the adsorption accompanied by a chemical reaction, it is possible to suppress the re-emission of the gas due to changes over time, which is preferable. The definition of a chemical reaction here means that the molecular structure of the gas changes when it is adsorbed.
[0018] Molecules composed of two or more types of atoms and having polarity tend to be more reactive than molecules composed of a single atom, and may cause health damage when inhaled into the body. In addition, molecules composed of multiple atoms tend to be polar, and therefore are more likely to undergo adsorption involving a chemical reaction in a gas adsorbing compound. Specific examples of such molecules include formaldehyde and ammonia, and the adsorption of formaldehyde is particularly important in building material applications such as building panels. Specific examples of atoms constituting the gas to be adsorbed include carbon, nitrogen, oxygen, sulfur, fluorine, chlorine, bromine, boron, phosphorus, and hydrogen, and are more preferably selected from carbon, nitrogen, oxygen, sulfur, fluorine, chlorine, and bromine, and are even more preferably selected from carbon, nitrogen, oxygen, and sulfur. The gas adsorbing compound may be a compound having the property of adsorbing a gas containing a molecule composed of three or more types of atoms.
[0019] In particular, the gas adsorbent compound is preferably a compound having an amino group and / or an imino group. By having an amino group or an imino group, it is possible to chemically react with polar gases such as formaldehyde and efficiently adsorb them. As such a gas adsorbent compound, an amine compound is preferable. Examples of the amine compound include aliphatic amines, aromatic amines, and heterocyclic amines. Specific examples of the amine compound include guanidine compounds, melamine compounds, urea compounds, hydrazide compounds, and polyethyleneimine compounds. Among these, it is preferable to have both an amino group and an imino group because of the high adsorption effect of formaldehyde, and from this viewpoint, a guanidine compound is preferable.
[0020] A guanidine compound is a compound having a guanidine skeleton in which one nitrogen atom is bonded to one carbon atom by a double bond and two nitrogen atoms are bonded to one carbon atom by a single bond. The guanidine compound is preferably a guanidine salt, which is a salt obtained by neutralizing guanidine represented by the rational formula HN=C(NH2)2 with an acid, and examples of the guanidine salt include guanidine phosphate, guanidine sulfate, guanidine hydrochloride, guanidine acetate, guanidine carbonate, and guanidine sulfamate. Among the guanidine salts, guanidine phosphate and guanidine sulfamate are preferred from the viewpoint of functioning as a flame retardant and excellent heat resistance, and guanidine phosphate is more preferred. The structural member of the present invention is characterized by being excellent in the loading amount of the gas adsorbing compound. From this viewpoint, it is preferable to select a flame retardant compound as the gas adsorbing compound, since it is possible to impart flame retardancy to the structural member.
[0021] In addition, when adsorbing a gas containing ammonia, the gas adsorbent is preferably a compound having a carboxyl group, and a specific example of such a gas adsorbent is polyacrylic acid.
[0022] In the present invention, the resin constituting the fiber reinforced resin may be either a thermosetting resin or a thermoplastic resin. From the viewpoint of the heat resistance of the resulting structural member, a thermosetting resin is preferred, and from the viewpoint of processability, a thermoplastic resin is preferred.
[0023] Examples of thermoplastic resins include polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyolefins such as polyethylene, polypropylene, polybutylene, and modified polypropylene, polyamides such as polyoxymethylene, polyamide 6, and polyamide 66, polycarbonate, polymethyl methacrylate, polyvinyl chloride, polyarylene sulfides such as polyphenylene sulfide, polyphenylene ether, modified polyphenylene ether, polysulfone, modified polysulfone, polyether sulfone, polyarylene ether ketones such as polyketone, polyether ketone, polyether ether ketone, and polyether ketone ketone, polyarylate, polyether nitrile, and phenoxy resin. Among these, polyarylene ether ketone is preferred from the viewpoint of heat resistance, and polyolefins are preferred from the viewpoint of cost and light weight. These thermoplastic resins may be copolymers, modified bodies, and / or blends of two or more types. In addition, it is also preferable that the thermoplastic resin contains other fillers and additives as appropriate within a range that does not impair the object of the present invention. Examples of the filler or additive include inorganic fillers, flame retardants, electrical conductivity imparting agents, crystal nucleating agents, ultraviolet absorbers, antioxidants, vibration dampers, antibacterial agents, insect repellents, deodorants, coloration inhibitors, heat stabilizers, release agents, antistatic agents, plasticizers, lubricants, colorants, pigments, dyes, foaming agents, foam control agents, and coupling agents.
[0024] Examples of thermosetting resins include unsaturated polyester, vinyl ester, epoxy resin, phenolic resin, urea resin, melamine resin, and thermosetting polyimide. Among these, epoxy resin is preferred from the viewpoint of curing speed, and phenolic resin is preferred from the viewpoint of cost and flame retardancy. These thermosetting resins may be copolymers, modified products, and / or blends of two or more types. In addition, the thermosetting resin may contain an impact resistance improver such as an elastomer or rubber component, and other fillers and additives, within a range that does not impair the object of the present invention. Examples of fillers and additives include the same materials as those of the thermoplastic resins described above.
[0025] Particularly preferred in the present invention is a structural member essentially made of a fiber-reinforced resin containing a phenolic resin as a resin. Phenol resins contain formaldehyde, which tends to be gradually released, which can be a problem. By forming the structural member of the present invention into a structure, it is possible to suppress the release of this formaldehyde, which is preferable. Specific examples of such phenolic resins include novolac-type phenolic resins and resol-type phenolic resins. As the phenolic resin, one of these may be used alone, or two or more types may be used in combination. As the phenolic resin, it is preferable to use a resol-type phenolic resin from the viewpoint of excellent impregnation into a reinforcing fiber substrate.
[0026] The novolac type phenolic resin can be appropriately selected according to the application, so long as it is a resin obtained by reacting phenols and aldehydes without a catalyst or in the presence of an acid catalyst. For example, random novolac type or high ortho novolac type phenolic resin can also be used. Note that this novolac type phenolic resin can usually be obtained by reacting while controlling the molar ratio of aldehydes to phenols (aldehydes / phenols) to be 0.5 or more and 1.0 or less.
[0027] Specific examples of phenols used in preparing the novolac phenolic resin include phenol, o-cresol, m-cresol, p-cresol, xylenol, alkylphenols, catechol, resorcin, etc. These phenols may be used alone or in combination of two or more.
[0028] Specific examples of aldehydes used in preparing the novolac phenolic resin include aldehyde compounds such as formaldehyde, paraformaldehyde, and benzaldehyde, as well as sources of these aldehyde compounds, or solutions of these aldehyde compounds. These aldehydes may be used alone or in combination of two or more.
[0029] Specific examples of acid catalysts used in preparing the novolac phenolic resin include organic carboxylic acids such as oxalic acid and acetic acid, organic sulfonic acids such as benzenesulfonic acid, paratoluenesulfonic acid, and methanesulfonic acid, and inorganic acids such as hydrochloric acid, sulfuric acid, and phosphoric acid. These may be used alone or in combination of two or more.
[0030] The resol type phenolic resin can be appropriately selected according to the purpose, so long as it is a resin obtained by reacting phenols with aldehydes in the presence of a basic catalyst. The resol type phenolic resin can usually be obtained by reacting the aldehydes with the phenols while controlling the molar ratio (aldehydes / phenols) to be 1.1 or more and 3.0 or less. Furthermore, from the viewpoint of the ease of curing of the obtained resol type phenolic resin, the molar ratio is preferably 1.3 or more and 1.7 or less.
[0031] Specific examples of phenols used in preparing this resol type phenolic resin include phenol, o-cresol, m-cresol, p-cresol, xylenol, alkylphenols, catechol, resorcin, etc. These phenols may be used alone or in combination of two or more.
[0032] Specific examples of aldehydes used in preparing the resol-type phenolic resin include aldehyde compounds such as formaldehyde, paraformaldehyde, and benzaldehyde, as well as sources of these aldehyde compounds, or solutions of these aldehyde compounds. These aldehydes may be used alone or in combination of two or more.
[0033] Specific examples of basic catalysts used in preparing resol-type phenolic resins include alkali metal hydroxides such as sodium hydroxide, lithium hydroxide, and potassium hydroxide, oxides and hydroxides of alkaline earth metals such as calcium, magnesium, and barium, sodium carbonate, aqueous ammonia, amines such as triethylamine and hexamethylenetetramine, and divalent metal salts such as magnesium acetate and zinc acetate. These may be used alone or in combination of two or more.
[0034] In the present invention, the resol type phenolic resin may be a self-curing type resin composition that does not contain a curing agent, or may contain a curing agent. By containing a curing agent, it can be cured in a short time and at a low temperature. For example, an acidic curing agent can be used as the curing agent. For example, organic or inorganic acids such as benzenesulfonic acid, paratoluenesulfonic acid, xylenesulfonic acid, phenolsulfonic acid, sulfuric acid, phosphoric acid, etc. can be used alone or in combination as the acidic curing agent. The amount of the acidic curing agent is appropriately determined, but from the viewpoint of achieving both the curability and stability of the resin composition, it is preferably 1 to 20 parts by mass, more preferably 3 to 15 parts by mass, and even more preferably 5 to 12 parts by mass, relative to 100 parts by mass of the resol type phenolic resin. If the amount of the acidic curing agent exceeds 20 parts by mass, it may be easy to gel in a short time and the usable time may not be sufficient. Also, if it is less than 1 part by mass, it may take too long to cure and may not be practical.
[0035] When the structural member of the present invention contains a phenolic resin as a resin, the structural member of the present invention preferably has a formaldehyde emission amount of 1.5 mg / L or less that can be measured by JIS A1460 (2021). The formaldehyde emission amount is more preferably 0 to 0.5 mg / L, and even more preferably 0 to 0.3 mg / L. By limiting the formaldehyde emission amount to such a range, the structural member of the present invention can be applied to various applications such as building materials such as building panels, which is preferable.
[0036] The reinforcing fibers in the fiber-reinforced resin constituting the structural member of the present invention are preferably discontinuous fibers having a number-average fiber length of 1 to 100 mm. The number-average fiber length is more preferably 1 to 20 mm, and even more preferably 3 to 10 mm. By setting the number-average fiber length in this range, it becomes easier to widen the intervals between fibers in the network structure of the nonwoven fabric form, and it becomes easier to control the formation of continuous pores. The number-average fiber length of the reinforcing fibers can be calculated by randomly selecting 400 reinforcing fibers, measuring their fiber lengths with an optical microscope, and dividing the total fiber length by the number of fibers measured. The fiber length can be measured, for example, by dissolving the fibers in an organic solvent or burning them off with an electric furnace to remove the resin components, and then filtering out the remaining reinforcing fibers and measuring them with an optical microscope.
[0037] Examples of reinforcing fibers include metal fibers such as aluminum, brass, and stainless steel; insulating fibers such as PAN-based, rayon-based, lignin-based, and pitch-based carbon fibers, graphite fibers, and glass; organic fibers such as aramid, PBO, polyphenylene sulfide, polyester, acrylic, nylon, and polyethylene; and inorganic fibers such as silicon carbide and silicon nitride. These fibers may be surface-treated. Surface treatments include, in addition to deposition of metal as a conductor, treatment with a coupling agent, treatment with a sizing agent, treatment with a bundling agent, and deposition of additives. These fibers may be used alone or in combination of two or more types. Among these, carbon fibers are preferred from the viewpoint of excellent balance between light weight and mechanical properties, and excellent springback properties described later, and PAN-based carbon fibers with an elastic modulus of 200 GPa or more are preferred. It is also preferable to use recycled carbon fibers from the viewpoint of cost. On the other hand, when fibers with low mechanical properties such as activated carbon fibers are used, the mechanical properties of the resulting structural members may be insufficient.
[0038] The diameter of the reinforcing fibers is preferably 1 to 20 μm, more preferably 3 to 10 μm, and even more preferably 6 to 8 μm. By setting the diameter in this range, the reinforcing fibers have excellent dispersibility, and when made into a nonwoven fabric, it is possible to achieve both high porosity and mechanical properties, which is preferable.
[0039] The amount of the gas adsorbent compound is preferably 1 to 1,000 parts by mass relative to 100 parts by mass of the reinforcing fiber. The amount of the gas adsorbent compound is more preferably 10 to 1,000 parts by mass, further preferably 100 to 1,000 parts by mass, and particularly preferably 500 to 1,000 parts by mass. If the amount of the gas adsorbent compound is greater than this range, the ratio of the film thickness of the gas adsorbent compound to the diameter of the reinforcing fiber increases, and the reinforcing effect of the reinforcing fiber may decrease. If the amount of the gas adsorbent compound is less than this range, the amount of the gas adsorbent compound occupying the porous surface may be small, and the gas adsorption effect may be insufficient.
[0040] In the structural member of the present invention, the gas adsorbent compound preferably forms a film having an average film thickness of 0.01 to 100 μm on the porous surface of the structural member. The film thickness is more preferably 5 to 100 μm, further preferably 15 to 100 μm, and particularly preferably 15 to 30 μm. If the film thickness is thicker than this range, the amount of continuous pores may be small, and the weight reduction effect may be insufficient. In addition, the specific surface area may be small, and the gas adsorption effect may be insufficient. If the film thickness is thinner than this range, the amount of gas adsorbent occupying the porous surface may be small, and the gas adsorption effect may be insufficient.
[0041] The structural member of the present invention has a density of 0.01 to 1 g / cm 3 The density is preferably 0.1 to 1 g / cm. 3 More preferably, 0.1 to 0.5 g / cm 3 More preferably, 0.3 to 0.5 g / cm 3 is particularly preferable. If the density is higher than the above range, the amount of interconnected pores in the structural member may be small, resulting in insufficient weight reduction. Also, the specific surface area of the structural member may be small, resulting in insufficient gas adsorption. If the density is lower than the above range, the volume of interconnected pores in the structural member may be too large, resulting in insufficient mechanical properties.
[0042] The structural member of the present invention preferably has a compressive modulus of 1 to 10,000 MPa. The compressive modulus is more preferably 10 to 10,000 MPa, further preferably 100 to 10,000 MPa, and particularly preferably 100 to 1,000 MPa. If the compressive modulus is greater than this range, the structural member may break brittle when subjected to an impact, resulting in scattering of fragments. If the compressive modulus is less than this range, the structural member may have insufficient mechanical properties.
[0043] The structural member of the present invention has the effect of absorbing harmful gases in the air, and therefore can be suitably used as a building material, particularly as a construction panel material, among other structural members.
[0044] <Manufacturing methods for structural components> As an example, the structural member of the present invention can be produced by a manufacturing method for a structural member including a step of springing back a prepreg containing reinforcing fibers and a resin to form a fiber-reinforced resin having a continuous porous structure, and a step of fixing a gas adsorbing compound having the property of adsorbing gas to the fiber-reinforced resin to form a structural member.
[0045] The prepreg containing reinforcing fibers and resin is preferably produced by impregnating a reinforcing fiber substrate in which discontinuous reinforcing fibers are processed into a nonwoven fabric form with a resin. FIG. 4 is a schematic diagram of one embodiment of the reinforcing fiber substrate of the present invention. In this embodiment, the reinforcing fibers 1 are randomly dispersed as discontinuous fibers, and are in the form of a nonwoven fabric forming a network structure, thereby forming fine continuous pores 3 between the fibers. Since the reinforcing fibers are in the form of a nonwoven fabric, the porosity can be designed to be higher than that of a woven fabric or a fiber substrate oriented in one direction, and this has the characteristic that the amount of resin or gas adsorbing compound impregnated can be increased. Examples of methods for producing a reinforcing fiber substrate in the form of a nonwoven fabric include an airlaid method, a carding method, and a papermaking method.
[0046] FIG. 5 is a schematic diagram showing one embodiment of the prepreg described above together with an enlarged view of a single yarn cross section of the reinforcing fiber. The thickness direction of the prepreg is called the out-of-plane direction 5, and the direction perpendicular to the out-of-plane direction is called the in-plane direction 6. From the viewpoint of short impregnation distance and excellent productivity, the prepreg in the present invention is preferably produced by impregnating the reinforcing fiber base material with resin while compressing it in the out-of-plane direction. In the prepreg, the resin 2 fills the space between the reinforcing fibers to form the prepreg. Examples of the production method of such a prepreg include a press molding method and an RTM molding method.
[0047] Next, such a prepreg is springbacked to form a fiber-reinforced resin having a continuous porous structure. The prepreg contains a reinforcing fiber substrate that is compressed in the out-of-plane direction during resin impregnation, and stores a repulsive force in the out-of-plane direction. Therefore, when the pressure in the out-of-plane direction is removed, the reinforcing fiber substrate releases the repulsive force and springs back to return to the original shape of the reinforcing fiber substrate. That is, the prepreg has an expandability in the out-of-plane direction. In the prepreg expanded in this way, the resin is further solidified or hardened to retain the shape, making it possible to mold it into a fiber-reinforced resin. In such a fiber-reinforced resin, typically, reinforcing fibers 1 form a randomly distributed network, the whole or part of the periphery is covered with resin 2, and the periphery is further occupied by continuous pores 3. Examples of a method for manufacturing such a fiber-reinforced resin include a press molding method and an RTM molding method.
[0048] From the viewpoint of impregnation with the gas adsorbing compound, the porosity of the fiber reinforced resin is preferably controlled to 10 to 85%. The porosity is more preferably 30 to 80%, and further preferably 50 to 70%. The porosity of the fiber reinforced resin is the proportion of pores in the fiber reinforced resin, and can be calculated by SEM observation of the cross section of the fiber reinforced resin using the following formula. (Porosity of fiber-reinforced resin) = (area of pores in observed cross section [μm 2 ]) / (area of observed cross section [μm 2 ])×100[%] The porosity can be adjusted by controlling the expansion ratio by adjusting the thickness of the mold used for springback. From the viewpoint of the balance between the light weight and mechanical properties of the resulting structural member, the expansion ratio is preferably 1.5 to 8 times, more preferably 2 to 6 times, and even more preferably 2 to 4 times.
[0049] The structural member of the present invention can be obtained by fixing the gas adsorbent compound to the fiber reinforced resin thus molded. In order to fix the gas adsorbent compound, it is preferable to impregnate the gas adsorbent compound into the continuous pores. There is no particular limitation on the impregnation method, and a method of impregnating the gas adsorbent compound in a powder or liquid form can be exemplified. In particular, when the resin is a phenolic resin, since the phenolic resin is hydrophilic, a method of impregnating the gas adsorbent compound as an aqueous solution and then evaporating the water can be preferably used. Examples of the impregnation method include a spray method and an immersion method. The spray method is a method of spraying an aqueous solution of the gas adsorbent compound in a mist form, and can be preferably used when it is desired to reduce the amount of the gas adsorbent to be fixed or when it is desired to partially fix the gas adsorbent compound as shown in FIG. 3. The immersion method is a method of immersing the fiber reinforced resin in an aqueous solution of the gas adsorbent compound, filling the aqueous solution into the continuous pores, and then evaporating the water. The immersion method can be preferably used when it is desired to increase the amount of the gas adsorbent fixed, when it is desired to obtain a structural member in which the gas adsorbent is fixed over the entire surface as shown in FIG. 2, or when it is desired to impregnate a thick fiber reinforced resin with the gas adsorbent. It is also preferable to repeat the immersion method two or more times. By impregnating a fiber reinforced resin having continuous pores with the gas adsorbent using the immersion method, it is possible to impregnate the gas adsorbent with a high loading amount. By highly loading the gas adsorbent, it is preferable because it is possible to suppress the emission of gas and improve the mechanical properties at the same time.
[0050] The structural member of the present invention can also be used as a laminate laminated with a sheet material. Examples of such sheet materials include a film made of the resin and a fiber-reinforced composite material made of the resin and the reinforcing fiber. Since the structural member has a gas adsorption effect, it is preferable that the laminated sheet material can adsorb the gas generated by the laminated sheet material. There is no particular restriction on the laminate structure, but from the viewpoint of the balance between light weight and mechanical properties, a sandwich structure in which the structural member of the present invention is sandwiched between a pair of sheet materials as a core material and integrated is preferred. In addition, from the viewpoint of excellent gas adsorption effect, a sandwich structure in which the sheet material is sandwiched between a pair of structural members of the present invention as a core material and integrated is also preferred.
[0051] The structural member of the present invention can be suitably used as a structural member for aircraft such as aircraft, artificial satellites, UAM (Urban Air Mobility), and drones, as well as automobile components, railway vehicle components, ship components, electronic device housings, sporting goods, and building materials. EXAMPLES
[0052] The materials used in the examples and comparative examples are as follows.
[0053] [Reinforced fiber] (A-1) Carbon fiber nonwoven fabric A carbon fiber bundle with a total of 12,000 single fibers was obtained by spinning, calcining, and surface oxidation of a copolymer mainly composed of polyacrylonitrile. The properties of this carbon fiber bundle were a tensile modulus of 220 GPa measured in accordance with JIS R7608 (2007), and a circular cross section with a single fiber diameter of 7 μm.
[0054] The carbon fiber bundle was cut into 6 mm lengths with a cartridge cutter to obtain chopped carbon fiber. A dispersion liquid with a concentration of 0.1% by mass was prepared from water and a surfactant (Polyoxyethylene lauryl ether (trade name) manufactured by Nacalai Tesques Co., Ltd.), and a carbon fiber nonwoven fabric was produced using this dispersion liquid and chopped carbon fiber. The manufacturing device is equipped with a cylindrical container with a diameter of 1000 mm having an opening and closing cock at the bottom of the container as a dispersion tank, and a linear transport section (inclined angle 30°) connecting the dispersion tank and the papermaking tank. A stirrer is attached to the opening on the top surface of the dispersion tank, and chopped carbon fiber and dispersion liquid (dispersion medium) can be charged from the opening. The papermaking tank is equipped with a mesh conveyor with a papermaking surface with a width of 500 mm at the bottom, and a conveyor capable of transporting carbon fiber nonwoven fabric (papermaking base material) is connected to the mesh conveyor. Papermaking was performed with a carbon fiber concentration in the dispersion liquid of 0.05% by mass. The paper base material is dried in a drying oven at 200°C for 30 minutes and the weight is 100g / m 2 The number average fiber length was measured and found to be 6 mm.
[0055] (A-2) Carbon fiber nonwoven fabric A carbon fiber nonwoven fabric was produced in the same manner as A-1, except that the process of cutting the carbon fiber into chopped carbon fiber with a cartridge cutter was replaced with a process of grinding the carbon fiber into milled carbon fiber. The carbon fiber nonwoven fabric thus obtained had a basis weight of 100 g / m 2 The number average fiber length was 0.1 mm.
[0056] (A-3) Carbon fiber fabric The carbon fiber bundles used in A-1 were woven into a plain weave fabric to obtain a carbon fiber fabric A-3 made of continuous fibers. The basis weight was 100 g / m 2 It was decided.
[0057] [resin] (B-1) Phenol resin A reactor equipped with a reflux condenser, a thermometer, and a stirrer was charged with 500 parts by mass of phenol, 527 parts by mass of a 50% aqueous formaldehyde solution, 38 parts by mass of water, and 25 parts by mass of a 50% aqueous sodium hydroxide solution, and reacted at 65°C for 120 minutes, at 90°C for 45 minutes, and at 75°C for 120 minutes, and then cooled to below 35°C to synthesize a resol-type phenolic resin. The molar ratio of formaldehyde / phenol [F / P] was 1.65.
[0058] The obtained phenolic resin was used with 100 parts by mass of added paratoluenesulfonic acid (p-toluenesulfonic acid monohydrate, manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) as an acidic curing agent.
[0059] (B-2) PP resin film 80% by mass of polypropylene (Prime Polymer Co., Ltd.'s "Prime Polypro" (registered trademark) J105G) and 20% by mass of acid-modified polypropylene (Mitsui Chemicals, Inc.'s "Admer" (registered trademark) QB510) were mixed in the above mass ratio as raw materials, melt-kneaded in a twin-screw extruder with a cylinder temperature of 200°C, and formed into a film with a basis weight of 200g / m. 2 A PP resin film was produced.
[0060] (B-3) PEKK resin film Polyetherketoneketone (Arkema's "KEPSTAN" (registered trademark) 6002) was used as the raw material, and the material was melt-kneaded in a twin-screw extruder at a cylinder temperature of 350°C, and formed into a film with a basis weight of 200 g / m. 2 A PEKK resin film was produced.
[0061] [Gas adsorbent compounds] (C-1) Guanidine phosphate Guanidine phosphate (guanidine phosphate, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used.
[0062] (C-2) Guanidine sulfamate Guanidine sulfamate (guanidine sulfamate, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used.
[0063] (C-3) Melamine Melamine (Melamine manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used.
[0064] (C-4) Polyethylene glycol Polyethylene glycol (polyethylene glycol 1,000, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used.
[0065] The methods for evaluating the structure, physical properties, etc. in each of the examples and comparative examples are as follows.
[0066] [Porosity of fiber-reinforced resin] The porosity of the fiber-reinforced resin is the proportion of pores in the fiber-reinforced resin, and was calculated using the following formula by SEM observation of the cross section of the fiber-reinforced resin. (Porosity of fiber-reinforced resin) = (area of pores in observed cross section [μm 2 ]) / (area of observed cross section [μm 2 ])×100[%] [Specific surface area of structural members] The mercury intrusion porosimeter was an Autopore IV9510 manufactured by Micromeritics, and measurements were carried out at mercury intrusion pressures ranging from 4 kPa to 400 MPa. The specific surface area was calculated from the following formula (1). (specific surface area) = 4 × (pore volume) / (average pore diameter) (1).
[0067] [Average thickness of gas adsorbent] The cross section of the structural member was observed by SEM, and the thickness of the gas adsorbing compound was measured. Measurements were taken at 50 locations for each sample, and the arithmetic mean of these thicknesses was taken as the average film thickness.
[0068] [Structural member density] The perimeter of the structural member sample was measured, and its volume ([cm 3 The mass ([g]) of the sample was then measured. The mass of the sample was divided by the volume of the sample to obtain the density ([g / cm 3 ]) was requested.
[0069] [Gas adsorbent coverage] The cross section of the structural member was observed by SEM. All pores in the obtained observation image were measured, and the perimeter of the pore and the length of the portion of the perimeter to which the gas adsorbent compound was attached were calculated. Furthermore, the coverage rate of the gas adsorbent compound was calculated by the following formula (2). (Gas adsorbent compound coverage [%]) = (total length of the perimeter where the gas adsorbent compound is attached [μm]) / (total perimeter of the pores [μm]) × 100 (2). Furthermore, the coverage rate of the gas adsorbent compound was evaluated according to the following three levels, with fair to good being considered a pass. Good: The coverage rate of the gas adsorbent is 90% or more and 100% or less. Fair: The coverage of gas adsorbent compounds is 50% or more but less than 90%. Bad: The coverage of the gas adsorbent is less than 50%.
[0070] [Compressive elastic modulus of structural members] The compressive modulus was measured by a compression test in accordance with JIS K7220 (2006) using an "Instron" (registered trademark) 5565 universal material testing machine (manufactured by Instron Japan Co., Ltd.). A test piece with a thickness of 50 mm in the out-of-plane direction and a width and length of 100 mm in the in-plane direction was cut out from the structural member, and a compression test was performed at room temperature and a test speed of 2 m / min. Five samples of each level were measured, and the arithmetic average value of the modulus of elasticity was used as the compressive modulus of the structural member. Furthermore, the compressive modulus was evaluated on the following four-point scale, with fair to excellent being considered a pass. Excellent: Compressive modulus of 100MPa or more. Good: Compressive elastic modulus is 10MPa or more and less than 100MPa. fair: Compressive elastic modulus is 1MPa or more and less than 10MPa. Bad: Compressive elastic modulus is less than 1 MPa.
[0071] [Formaldehyde emission rate] Formaldehyde emission was measured in accordance with JIS A1460 (2021). It was evaluated on a four-point scale, with fair to excellent being considered a pass. Excellent: Formaldehyde emission level is less than 0.3mg / L. Good: Formaldehyde emission level is greater than 0.3 mg / L and less than 0.5 mg / L. fair: Formaldehyde emission level is greater than 0.5 mg / L and less than 1.5 mg / L. Bad: Formaldehyde emission is greater than 1.5 mg / L.
[0072] [Formaldehyde adsorption] A structural member sample measuring 150mm x 150mm x 50mm was placed in a 9L desiccator. Air containing formaldehyde at a concentration of 1ppm was then injected into the desiccator. Formaldehyde adsorption was evaluated on a three-point scale, with fair to good being considered a pass. Good: There was no odor when the desiccator was opened after 24 hours. fair: There was an odor when the desiccator was opened after 24 hours, but there was no odor when the desiccator was opened after 72 hours. Bad: There was an odor when the desiccator was opened after 24 hours and after 72 hours.
[0073] [Ammonia adsorption] A structural member sample measuring 150 mm x 150 mm x 50 mm was placed in a 9 L desiccator. Air containing ammonia at a concentration of 1 ppm was then injected into the desiccator. Ammonia adsorption was evaluated on a three-point scale, with fair to good being considered a pass. Good: There was no odor when the desiccator was opened after 24 hours. fair: There was an odor when the desiccator was opened after 24 hours, but there was no odor when the desiccator was opened after 72 hours. Bad: There was an odor when the desiccator was opened after 24 hours and after 72 hours.
[0074] The structural members produced in the examples and comparative examples will be described below.
[0075] [Example 1] (Reinforced Fiber) As the reinforcing fiber, 50 sheets of A-1 carbon fiber nonwoven fabric cut to a width of 300 mm and a length of 300 mm were laminated and used.
[0076] (resin) As the resin, 1,350 g of phenolic resin B-1 was used.
[0077] (Gas Adsorbent Compounds) As the gas adsorbent compound, C-1, guanidine phosphate, was used.
[0078] Resin was applied to the above-mentioned reinforcing fibers and press-molded at 30°C and 7 MPa for 3 minutes to produce an expandable prepreg with a thickness of 15 mm.
[0079] The prepreg was transferred into a mold with a cavity thickness of 50 mm, and press molding was performed by controlling the expansion ratio to 3 times. The mold temperature was set to 60°C, and the mold was heated for 120 minutes in a closed state to harden the resin. The mold was then opened, and the fiber-reinforced resin was taken out.
[0080] The fiber-reinforced resin was immersed in an aqueous solution of 5% by mass of the gas-adsorbing compound for 30 minutes. The fiber-reinforced resin was then removed and dried in a hot air dryer at 150° C. for 60 minutes to obtain a structural member. The results of each evaluation are shown in Table 1.
[0081] [Example 2] The number of sheets of A-1 was 30, the amount of B-1 was 810 g, and the aqueous solution concentration of C-1 was changed to 2.5 mass%. The thickness of the prepreg was 10 mm and had expandability, and the expansion ratio was controlled to 5 times to make a fiber reinforced resin of 50 mm. A structural member was obtained in the same manner as in Example 1 except for that. The results of each evaluation are shown in Table 1.
[0082] [Comparative Example 1] The number of sheets of A-1 was 165, and the amount of B-1 was 4,455 g. The thickness of the prepreg was 50 mm, and it had expandability, so the expansion ratio was controlled to 1 to make a 50 mm fiber reinforced resin. Otherwise, a structural member was obtained in the same manner as in Example 1. The results of each evaluation are shown in Table 1.
[0083] [Comparative Example 2] Except for using A-2 instead of A-1, molding was performed in the same manner as in Comparative Example 1. The thickness of the obtained prepreg was 50 mm, and since it had no expansibility, molding was performed with an expansion ratio of 1. The results of each evaluation are shown in Table 1.
[0084] [Comparative Example 3] Except for using A-3 instead of A-1, molding was performed in the same manner as in Comparative Example 1. The thickness of the obtained prepreg was 50 mm, and since it had no expansibility, molding was performed with an expansion ratio of 1. The results of each evaluation are shown in Table 1.
[0085] [Comparative Example 4] Except for changing the amount of B-1 to 5,400 g, molding was performed in the same manner as in Example 1. The thickness of the obtained prepreg was 50 mm, and since it had no expansibility, molding was performed with an expansion ratio of 1. The results of each evaluation are shown in Table 1.
[0086] [Example 3] Molding was carried out in the same manner as in Example 1, except that C-2 was used instead of C-1. The thickness of the obtained prepreg was 15 mm and had expandability, and the expansion ratio was controlled to 3 times in order to make it a fiber reinforced resin with a thickness of 50 mm. The results of each evaluation are shown in Table 1.
[0087] [Example 4] C-3 was used instead of C-1. Since C-3 was not water-soluble, it was crushed into particles with an average particle size of 2 μm and dispersed in water to form an emulsion. Otherwise, molding was performed in the same manner as in Example 1. The thickness of the obtained prepreg was 15 mm and had expandability, and the expansion ratio was controlled to 3 times in order to make it into a fiber reinforced resin with a thickness of 50 mm. The results of each evaluation are shown in Table 1.
[0088] [Comparative Example 5] Molding was carried out in the same manner as in Example 1, except that C-4 was used instead of C-1. The thickness of the obtained prepreg was 15 mm and had expandability, and the expansion ratio was controlled to 3 times in order to make it a fiber reinforced resin with a thickness of 50 mm. The results of each evaluation are shown in Table 1.
[0089] [Comparative Example 6] Molding was performed in the same manner as in Example 1, except that C-1 was omitted and no gas adsorbing compound was used. The thickness of the obtained prepreg was 15 mm and had expandability, and the expansion ratio was controlled to 3 times in order to make it a fiber reinforced resin with a thickness of 50 mm. The results of each evaluation are shown in Table 1.
[0090] [Comparative Example 7] The amount of B-1 was 135g, C-1 was eliminated, and no gas adsorbent compound was used. The prepreg had a thickness of 4mm and was expandable, and the expansion ratio was controlled to 12 times to make a fiber reinforced resin with a thickness of 50mm. Other than that, a structural member was obtained in the same manner as in Example 1. The results of each evaluation are shown in Table 1.
[0091] [Example 5] The concentration of C-1 in the aqueous solution was changed to 50% by mass. Otherwise, a structural member was obtained in the same manner as in Example 1. The results of each evaluation are shown in Table 1.
[0092] [Example 6] The concentration of the aqueous solution of C-1 was changed to 50 mass%. Furthermore, the fiber reinforced resin was immersed in this aqueous solution for 30 minutes, then taken out and dried by heating in a hot air dryer at 150°C for 60 minutes. This immersion process was repeated twice to obtain a structural member. Otherwise, the structural member was obtained in the same manner as in Example 1. The results of each evaluation are shown in Table 1.
[0093] [Table 1]
[0094] [Example 7] A structural member was molded in the same manner as in Example 1. The obtained prepreg had a thickness of 15 mm and was expandable, and the expansion ratio was controlled to 3 times in order to make a fiber reinforced resin having a thickness of 50 mm. The results of each evaluation are shown in Table 2.
[0095] [Example 8] Molding was carried out in the same manner as in Example 7, except that C-5 was used instead of C-1. The thickness of the obtained prepreg was 15 mm and had expandability, and the expansion ratio was controlled to 3 times in order to make it a fiber reinforced resin with a thickness of 50 mm. The results of each evaluation are shown in Table 2.
[0096] [Comparative Example 8] Molding was performed in the same manner as in Example 7, except that C-1 was omitted and no gas adsorbing compound was used. The thickness of the obtained prepreg was 15 mm and had expandability, and the expansion ratio was controlled to 3 times in order to make it a fiber reinforced resin with a thickness of 50 mm. The results of each evaluation are shown in Table 2.
[0097] [Example 9] (Reinforced Fiber) As the reinforcing fiber, 50 sheets of A-1 carbon fiber nonwoven fabric cut to a width of 300 mm and a length of 300 mm were laminated and used.
[0098] (resin) As the resin, 75 sheets of B-2 PP resin film were used.
[0099] (Gas Adsorbent Compounds) As the gas adsorbent compound, C-1, guanidine phosphate, was used.
[0100] The above-mentioned reinforcing fiber and resin laminate was press-molded and pressurized at 7 MPa at 200°C for 30 minutes, then cooled to 30°C and removed to produce an expandable prepreg with a thickness of 19 mm.
[0101] The prepreg was transferred into a mold with a cavity thickness of 50 mm, and press molding was performed by controlling the expansion ratio to 3 times. The mold temperature was first heated to 200°C for 30 minutes, and then cooled to 30°C to solidify the resin. The mold was then opened, and the fiber-reinforced resin was removed.
[0102] The fiber-reinforced resin was immersed in an aqueous solution of 5% by mass of the gas-adsorbing compound for 30 minutes. The fiber-reinforced resin was then removed and dried in a hot air dryer at 150° C. for 60 minutes to obtain a structural member. The results of each evaluation are shown in Table 2.
[0103] [Comparative Example 9] Molding was performed in the same manner as in Example 9, except that C-1 was omitted and no gas adsorbing compound was used. The thickness of the obtained prepreg was 19 mm and had expandability, and the expansion ratio was controlled to 3 times in order to make it a fiber reinforced resin with a thickness of 50 mm. The results of each evaluation are shown in Table 2.
[0104] [Example 10] (Reinforced Fiber) As the reinforcing fiber, 50 sheets of A-1 carbon fiber nonwoven fabric cut to a width of 300 mm and a length of 300 mm were laminated and used.
[0105] (resin) As the resin, 75 sheets of B-3 PEKK resin film were used.
[0106] (Gas Adsorbent Compounds) As the gas adsorbent compound, C-1, guanidine phosphate, was used.
[0107] The above-mentioned reinforcing fibers and resin were laminated and pressurized at 350°C and 7 MPa for 30 minutes, then cooled to 30°C and removed to produce an expandable prepreg with a thickness of 15 mm.
[0108] The prepreg was transferred into a mold with a cavity thickness of 50 mm, and press molding was performed by controlling the expansion ratio to 3 times. The mold temperature was first heated to 350°C for 30 minutes, and then cooled to 30°C to solidify the resin. The mold was then opened, and the fiber-reinforced resin was removed.
[0109] The fiber-reinforced resin was immersed in an aqueous solution of 5% by mass of the gas-adsorbing compound for 30 minutes. The fiber-reinforced resin was then removed and dried in a hot air dryer at 150° C. for 60 minutes to obtain a structural member. The results of each evaluation are shown in Table 2.
[0110] [Comparative Example 10] Molding was performed in the same manner as in Example 10, except that C-1 was omitted and no gas adsorbing compound was used. The thickness of the obtained prepreg was 15 mm and had expandability, and the expansion ratio was controlled to 3 times in order to make it a fiber reinforced resin with a thickness of 50 mm. The results of each evaluation are shown in Table 2.
[0111] [Example 11] Molding was performed in the same manner as in Example 7, except that the process of immersing the fiber-reinforced resin in the aqueous solution of the gas adsorbing compound was changed to a process of spraying the aqueous solution onto the fiber-reinforced resin with a sprayer. The results of each evaluation are shown in Table 2.
[0112] [Table 2] [Explanation of symbols]
[0113] 1 Reinforced Fiber 2. Resin 3 Continuous voids 4. Gas-adsorbing compounds 5 Out-of-plane direction 6 In-plane directions
Claims
1. A structural member consisting essentially of a porous fiber-reinforced resin containing reinforcing fibers, resin, and continuous pores, wherein the resin is present in an amount of 100 to 1,000 parts by mass per 100 parts by mass of the reinforcing fibers, and a gas adsorbent compound is fixed to the porous surface facing the continuous pores.
2. The structural member of claim 1 , wherein the resin comprises a phenolic resin.
3. 3. The structural member according to claim 2, wherein the gas adsorbent compound is a compound having an amino group and / or an imino group.
4. 4. The structural member according to claim 3, wherein the gas adsorbent compound comprises an amine compound selected from the group consisting of a guanidine compound, a melamine compound, a urea compound, a hydrazide compound, and a polyethyleneimine compound.
5. 5. The structure of claim 4, wherein the amine compound comprises a guanidine compound selected from the group consisting of guanidine phosphate, guanidine sulfate, guanidine hydrochloride, guanidine acetate, guanidine carbonate, and guanidine sulfamate.
6. The structural member according to claim 5, having a formaldehyde emission amount measured according to JIS A1460 (2021) of 1.5 mg / L or less.
7. 2. The structural member of claim 1, wherein the gas adsorbing compound comprises a compound that adsorbs ammonia.
8. Specific surface area measured by mercury porosimetry is 0.01 to 0.5 m 2 The structural member according to any one of claims 1 to 7, wherein the elastic modulus is 1 / g.
9. The structural member according to any one of claims 1 to 7, wherein the gas adsorbing compound is 1 to 1,000 parts by mass per 100 parts by mass of the reinforcing fibers.
10. 8. The structural member according to claim 1, wherein said gas adsorbent compound forms a film having an average film thickness of 0.01 to 100 μm on said porous surface.
11. The structural member according to any one of claims 1 to 7, wherein the reinforcing fibers are discontinuous carbon fibers having a number average fiber length of 1 to 100 mm.
12. A structural member which is a laminate comprising the structural member according to any one of claims 1 to 7 and a sheet material.
13. The structural member according to any one of claims 1 to 7, which is used as an aircraft member, an automobile member, a railway vehicle member, a ship member, an electronic device housing, a sporting goods, or a building material.
14. A method for manufacturing a structural member, comprising: a step of causing a prepreg containing reinforcing fibers and a resin to spring back to form a fiber-reinforced resin having a continuous porous structure; and a step of fixing a gas adsorbent compound having the property of adsorbing gas to the fiber-reinforced resin to form a structural member.
15. The method for producing a structural member according to claim 14, further comprising the step of impregnating a reinforcing fiber substrate containing the reinforcing fibers with the resin to form a prepreg.
Citation Information
Patent Citations
Structural body
WO2017110528A1